Pengetahuan, Sikap, dan Perilaku Masyarakat dalam Memilih Obat yang Aman di Tiga Provinsi di Indonesia - Siahaan, Selma; Usia, Tepy; Pujiati, Sri; Tarigan, Ingan Ukur; Murhandini, Sri; Isfandari, Sitti; Tiurdinawati, Tiurdinawati (Jurnal Kefarmasian Indonesia, 2017)
Medicine is an important component that cannot be replaced in health service. Indonesia National Agency of Drug and Food Control conducted survey to assess knowledge, attitude, and practice (KAP) of communities on selecting safe and quality medicines. The aim of the study is to get description KAP of community in choosing a safe medicine. Data were collected in West Java, DKI Jakarta, and South East Sulawesi. Sampling calculation use probability proportional to size sampling and census block. There were 1271 households as samples that analysed. Data results were analysed using descriptive and index analysis. Knowledge relates to criteria of quality medicines, rules for antibiotics use, and medicines logo. Attitude relates to how to select over the counter medicines, reasons of taking traditional medicines, and opinion about giving half dose of adults medicines to children. Practice relates to source of medicines information, the way to buy prescribe medicines, and reading label information. The results showed that KAP of communities on selecting safe and quality medicines close to 50%. According to score of index analysis are 4.65 (1 to 10 scale), it is recommended that information, education, and communication has to be delivered to communities intensively and continuously by the government.